2021
DOI: 10.3390/app11199343
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin Improves Dexamethasone-Impaired Wound Healing In Vitro and In Vivo by Enhancing Keratinocyte Proliferation and Migration

Abstract: The delayed and impaired wound healing caused by dexamethasone (DEX) is commonly reported. Puerarin, the major isoflavone found in Pueraria montana var. lobata (Willd.) Sanjappa & Pradeep promoted the wound healing process in diabetic rats. However, the effects and underlying mechanisms of puerarin on DEX-impaired wound healing have not been investigated. This study examined the potential uses of puerarin in upregulating keratinocyte proliferation and migration in dexamethasone (DEX)-suppressed wound heali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…Re-epithelialization was achieved through cell migration of keratinocytes. 28 In this study, epidermal thickness around the wound was observed by H&E staining, as shown in Fig. 3A.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Re-epithelialization was achieved through cell migration of keratinocytes. 28 In this study, epidermal thickness around the wound was observed by H&E staining, as shown in Fig. 3A.…”
Section: Discussionmentioning
confidence: 71%
“…In the hemostatic phase, some growth factors were released to accelerate skin resurfacing and neovascularization, such as transforming growth factors. 28 The formation of collagen fibers cross-linking also enhanced the tensile strength of the tissue. 30,31 Hence, SCP has a beneficial capacity for cell and tissue proliferation.…”
Section: Papermentioning
confidence: 99%
“…The effects of SSP-AuNPs on the viability of HaCaT cells were examined using MTT assays. 34 HaCaT cells were seeded at a density of 5×10 4 cells/well to 96-well plates. After 24 h, cells were treated with SSP-AuNPs (5, 10, 25 µg/mL) for 24 h. After treatment, the culture medium was removed, then 100 µL fresh medium and 10 µL of MTT reagent (5 mg/mL) (Sigma-Aldrich, St. Louis, MO, USA) were added to each well.…”
Section: Methodsmentioning
confidence: 99%
“…For scratch wound assay of SSP-AuNPs, the HaCaT cells were seeded at a density of 4×10 5 cells/well on 12-well plates and allowed to achieve 100% confluence. 34 , 35 Then, the cells were scratched and treated with SSP-AuNPs samples (5, 10, 25 µg/mL) or Centella asiatica extract (positive control, 100 µg/mL; United States Pharmacopeia (USP) Reference Standard, purchased from Sigma Aldrich). The images of scratch gap width for each time-point were captured by Lionheart FX Automated imaging system and measured using Gen5 Imager software (Biotek Instruments Inc., Winooski, VT, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Puerarin promotes keratinocyte proliferation and migration by activating ERK and Akt signaling pathways in DEX-treated HaCaT cells. In a nutshell, puerarin effectively reversed the deferred and interrupted wound healing connected with to the DEX treatment mechanism [ 126 ]. Puerarin can prevent LPS-induced vascular endothelial injury, and the mechanism may be connected with the restraint of NF-κB activation, then changing the levels of inflammatory factors and clotting-relevant factors [ 127 ].…”
Section: The Role Of Puerarin In Inflammatory Diseasesmentioning
confidence: 99%